Myopia control with contact lenses in children: a systematic review - Cruz, Catarina (2023)
Introduction – Myopia is defined as an excess of positive power in the eye’s optical system, resulting in an image that focuses anteriorly to the retinal plane. It is considered a public health problem; therefore, it becomes relevant to investigate therapies that control its progression. Objectives – This systematic review aims to compare the effectiveness of treatments in the reduction of myopia progression in children with soft contact lenses (SCL) and orthokeratology lenses (OKL). Methods – Scientific articles were searched on PubMed and ScienceDirect platforms. All articles were screened according to PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-analyses) and the pre-determined inclusion and exclusion criteria. The treatment efficacy was evaluated by the axial length (AL) variation and/or the refractive error variation measured by cycloplegia (spherical equivalent, SE) between the beginning and the end of the study and between the groups of treatment and controls. Results – Thirteen articles were included and divided into two groups. In the OKL group (n=5), eight lenses were studied and their effectiveness in AL progression varied between 0,45mm and 0.09mm. In the SCL group (n=8), 11 lenses were studied and their effectiveness in AL progression ranged from 0.32mm to 0.09mm and in SE progression ranged from 0.14 D to 0.73 D. Conclusion – Of all the OKL, the one that showed the greatest efficacy in the progression of AL was Menicon Z Night® lens (OKL): 0.45mm. Of all the SCL, MiSight 1-Day® was the most effective in decreasing both AL and SE progression: 0.32mm and 0.73 D respectively.